2021
DOI: 10.1103/physrevb.103.214506
|View full text |Cite
|
Sign up to set email alerts
|

Normal state specific heat in the cuprate superconductors La2xSrxCuO4 and Bi2

Abstract: The specific heat C of the cuprate superconductors La2−xSrxCuO4 and Bi2+ySr2−x−yLaxCuO6+ was measured at low temperatures (down to 0.5 K) for dopings p close to p, the critical doping for the onset of the pseudogap phase. A magnetic field up to 35 T was applied to suppress superconductivity, giving direct access to the normal state at low temperatures, and enabling a determination of Ce, the electronic contribution to the normal-state specific heat at T→0. In La2−xSrxCuO4 at x=p=0.22, 0.24 and 0.25, Ce/T=15to1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 44 publications
10
23
0
Order By: Relevance
“…Data at H = 10 and 15 T are practically superimposed, which indicates that the normal state is very nearly reached in the bulk. (Measurements of the specific heat on the same two samples show that the critical field for OD10K is indeed 15 T, while it is ∼25 T for OD18K [52].) This is reminiscent of what was found in Nd-LSCO, in which the normal state in thermal conductivity measurements was also reached at a smaller field than in electric transport measurements [20].…”
Section: Thermal Conductivitysupporting
confidence: 69%
See 2 more Smart Citations
“…Data at H = 10 and 15 T are practically superimposed, which indicates that the normal state is very nearly reached in the bulk. (Measurements of the specific heat on the same two samples show that the critical field for OD10K is indeed 15 T, while it is ∼25 T for OD18K [52].) This is reminiscent of what was found in Nd-LSCO, in which the normal state in thermal conductivity measurements was also reached at a smaller field than in electric transport measurements [20].…”
Section: Thermal Conductivitysupporting
confidence: 69%
“…In Eu-LSCO, Nd-LSCO and Bi2201 a log(1/T ) divergence is also observed in the electronic specific heat, (C el /T ), at p [17,52]. This thermodynamic evidence of quantum criticality, combined with the T -linear resistivity, suggests that the log(1/T ) dependence of the Seebeck coefficient is also a signature of quantum criticality, as found in some theoretical models [65].…”
Section: Seebeck Coefficient: Logarithmic Divergencesupporting
confidence: 58%
See 1 more Smart Citation
“…The single-layer cuprate superconductor La 2−x Sr x CuO 4 (LSCO) can be doped across the superconducting phase diagram, where the hole doping p = x. Normal-state heat-capacity measurements have been made at T ≈ T c [16,17] and also at lower temperatures with superconductivity suppressed by Zn doping [18], a high magnetic field [19], or a high magnetic field and Nd/Eu doping [14]. It is found that the specific heat γ(p) shows a peak at p = p c ≈ 0.22 (see Fig.…”
mentioning
confidence: 99%
“…Thus, it is natural to ask whether spin fluctuations contribute to the large γ values near p c in LSCO. The situation in LSCO is subtle because the Fermi energy E F passes through a van-Hove singularity (VHS) [6,7] near p c as the doping is increased and the pseudogap [11] terminates at a critical doping p ≈ 0.19 [13,19] which is close to p c .…”
mentioning
confidence: 99%